KEMAMPUAN MENGARANG DESKRIPSI BERDASARKAN OBSERVASI PADA SISWA KELAS V SDN 1 GULAK GALIK BANDAR LAMPUNG - Rachmasisca, Frieska Maryova (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2020)
The problem discussed in this study was the ability to write descriptions of the Odd Semester Class of SD Negeri 1 Gulak Galik in Bandar Lampung. The research method used is descriptive qualitative method. The research sample of 30 students was taken using a stratified proportional random sampling technique from the existing population. The data collection technique was carried out by means of a performance test, which assigned students a description of the object in the school environment. Data analysis used quantitative analysis using a simple percentage formula. The results showed that the ability to write descriptions of class V Odd Semester SD Negeri 1 Gulak galik Bandar Lampung with a sufficient category with a score of 67. Of the 5 aspects that were assessed there was 1 aspect of content suitability with a score of 87.5 declared very good, 3 aspects were sufficient, namely aspects of spelling writing, written form and sentence effectiveness, and 1 aspect which is stated to be lacking in the aspect of word choice.